Design, synthesis and evaluation of unique 2,4,5-triaryl imidazole derivatives as novel potent aspartic protease inhibitors - Khan, Mohd Sajid; Akhtar, Salman; Siddiqui, S. A.; Siddiqui, M. S.; Srinivasan, K. V.; Arif, J. M. (Medicinal Chemistry, 2012)
The 2,4,5-triaryl imidazole derivatives (API) were designed, screened and characterized kinetically & thermo-dynamically against Pepsin and their activity was also tested on the in silico platform. The docking studies of API with Pepsin show that these are novel and unique inhibitors of Aspartic protease. Drug like properties of these compounds were validated in silico based on Lipinski's rule of Five by calculating ClogP, LogS, H-bond acceptors, H-Bond donors, rotational bonds, PSA, PB and BBB values. The Et/Ki and Et/Km values of API show that they follow the Michaelis-Menten kinetics. The binding of inhibitors with proteases was explained by using Van't Hoff plot and thermodynamic parameters viz. free energy (Delta G), Entropy (Delta S) and Enthalpy (Delta H). The Van't Hoff analysis showed that the value of K-i decreases with increase in temperature and the binding of the inhibitor are entropically driven. API act as new potent aspartic protease inhibitors with K-i, for Pepsin, ranges from 3.7 mu M to 16.7 mu M. Strong hydrophobic groups at C-4 & C-5 position in API favor binding of inhibitors with Pepsin. Experiments also showed that among C-2 aryl substituted imidazole, a 4-substitution on aryl ring is preferred and less polar substituent makes the molecule more active whereas polar substituents at 2-position on C-2 aryl ring makes the molecule less active. The docking studies of API with Pepsin further intensify and validate our results.
Keywords: 2; 4; 5-triaryl imidazole derivatives; docking; Lipinski's rule of Five; Protease inhibitors; Thermodynamics